Penggunaan Metode Rasio Absorban dalam Penetapan Kadar Parasetamol dan Salisilamida Berbentuk Sediaan Campuran - Armin, Fithriani; Rusdi, Rusdi; Dantes, Ehrlich Von (Fakultas Farmasi Universitas Andalas, 2012)
A study on the determination of paracetamol and salicylamide in a mixture by absorbance ratio method has been done. The absorption spectrum of both compounds crossing one each other at isoabsorption point. The maximum wavelength of paracetamol, salicylamide, and wavelength of isoabsorpsi line which show the relation of paracetamol fractions in a mixture containing paracetamol and salicylamide in various proportions and absorbances at isoabsorption wavelength was constructed. The measurement of absorbance was done at 247,2 nm and 300,3 nm. The experiment showed that the absorbancy ratio method can be used to determine paracetamol and salicilamyde. The percent recovery of paracetamol was 101,31 % with 0,642 % of standard deviation and coefficient of variation 0,616 %. The salicylamide content was then calculated and found to be 99,66 % with 0,863 % of standard deviation and 0,861 % of coefficient variation.